The waiting room as a space for health promotion in the psychosocial care center (Research, Society and Development, 2020)
Medicines are considered one of the effective therapeutic forms in the treatment of psychiatric disorders and are widely used in the Psychosocial Care Center (CAPS), however, psychotropics are frequent causes of drug intoxication and other health problems. This report aims to discuss the experience of an educational action carried out in a CAPS waiting room in a municipality in the interior of Ceará, developed by students from the 6th semester of the undergraduate nursing course, whose main theme was guidance related to the use of psychotropic drugs. The practice took place by making a self-explanatory poster and dynamics of interaction between the institution's clients, with a focus on removing doubts and using accessible language for greater understanding. Taking into account the significant increase in the use of psychotropics in the treatment of psychiatric disorders, it is understood how much it is necessary for professionals to monitor and be attentive to possible patient placements, so that they feel capable and comfortable to expose their doubts, preventing clients from making therapy changes on their own. Therefore, the waiting room presents itself as a fundamental and initial approach that allows the development of future practices and interventions aimed at the client, enabling the promotion of health and self-care in the context of mental health.